Health Status of Children in Assam - Chayanika Goswami (Indian Journal of Forensic Medicine & Toxicology, 2020)
Children are the most valuable asset of a nation; their good health is the cornerstone for survival and development for current and succeeding generations which guarantee the sound and sustained economic development. Child health is a state of social, emotional, intellectual, mental and physical well- being which does not merely represent the absence of disease or infirmity. The term nutrition refers to a process of attaining necessary food for proper health and growth of human being. The nutritional status of children impacts their health, cognition and educational achievements. But underweight and malnutrition are most prominent health indicators in India and also in Assam (According to NFHS-3 & NFHS-4). Assam is situated in the North-East of India, bearing a considerable percentage of its population under the poverty line. Assam does not have shown much improvement in its health and nutrition indicators. Almost 36.4 percent children under age 5 are stunted and Infant Mortality Rate as high as 48( NFHS-4). The health status of children in rural areas of Assam is very pathetic. 55 percent children are stunting in rural areas. Various reports states that though Assam has made progress in its health indicators, still there is a great need to strengthen its existing health care services especially in the rural areas. The present study has made an attempt to study the health status of children in Assam. This study may be able to provide a base line information and need for effective implementation of various schemes and programmes for the improvement of health status of children in future.